Steel designers' handbook - Gorenc, B. (NewSouth Publishing, 2012)
Fully revised and updated, this eighth edition is an invaluable tool for all practicing structural, civil, and mechanical engineers as well as engineering students. Responding to changes in design and processing standards-including fabrication, welding, and coatings-this resource introduces the main concepts of designing steel structures; describes the limit states method of design; demonstrates the methods of calculating the design capacities of structural elements and connections; and illustrates the calculations by means of worked examples.
Keywords: Civil engineering -- Handbooks, manuals, etc.; Steel, Structural -- Handbooks, manuals, etc.; Structural design -- Handbooks, manuals, etc.; elektronické knihy; electronic books